The War That Never Ends : New Perspectives on the Vietnam War - Anderson, David L., 1946-; Ernst, John, 1962- (Book collections on Project MUSE., 2007)
More than three decades after the final withdrawal of American troops from Southeast Asia, the legacy of the Vietnam War continues to influence political, military, and cultural discourse. Journalists, politicians, scholars, pundits, and others have used the conflict to analyze each of America's subsequent military engagements. Many Americans have observed that Vietnam-era terms such as ""cut and run,"" ""quagmire,"" and ""hearts and minds"" are ubiquitous once again as comparisons between U.S. involvement in Iraq and in Vietnam seem increasingly appropriate. Because of its persistent signific.